Intrapersonal Intelligence: Differentiated Learning Builds Human Resources with Superior Education - Eddy Saputra; Atabik Luthfi; Fery Rahmawan Asma; Jenal Abidin; Nur Ali; Hasan Özalp (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2025)
Differentiated learning is student-centered learning that can be used as a habit to increase intrapersonal intelligence in education to produce superior human resources through education. Teachers as facilitators have a central role in understanding students' learning needs, including the development of intrapersonal intelligence, which is an important aspect in shaping individual character and abilities. This study aims to examine the role of teachers in implementing differentiated learning to develop students' intrapersonal intelligence. Through a qualitative approach, this study was conducted through observation, interviews, and document studies in a vocational high school environment. The results of the study indicate that teachers who are able to recognize the unique potential of each student and create an adaptive learning environment can improve students' self-awareness, emotional management, and decision-making. Effective differentiated learning has also been found to motivate students to explore their potential, thus supporting the creation of HR who are not only intellectually competent but also have strong intrapersonal skills. Researchers as facilitators in improving teacher competency in P4 Central Jakarta for vocational high school teachers.